2008
DOI: 10.1101/gr.076588.108
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of new genes in Drosophila

Abstract: Several mechanisms have been proposed to account for the origination of new genes. Despite extensive case studies, the general principles governing this fundamental process are still unclear at the whole-genome level. Here, we unveil genome-wide patterns for the mutational mechanisms leading to new genes and their subsequent lineage-specific evolution at different time nodes in the Drosophila melanogaster species subgroup. We find that (1) tandem gene duplication has generated ∼80% of the nascent duplicates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
257
6
4

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(289 citation statements)
references
References 88 publications
(124 reference statements)
22
257
6
4
Order By: Relevance
“…Prior to this study, there were few reports of novel gene origination by this mechanism and none identified human-specific genes (Levine et al 2006;Begun et al 2007;Cai et al 2008;Zhou et al 2008;Toll-Riera et al 2009). The novel proteins identified in this study are all short, encoded by an uninterrupted ORF, are supported by expression data, and the corresponding regions of chromosome where the ortholog is expected to be found in chimp and macaque harbor disabling mutations, which mean that the protein cannot be produced.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior to this study, there were few reports of novel gene origination by this mechanism and none identified human-specific genes (Levine et al 2006;Begun et al 2007;Cai et al 2008;Zhou et al 2008;Toll-Riera et al 2009). The novel proteins identified in this study are all short, encoded by an uninterrupted ORF, are supported by expression data, and the corresponding regions of chromosome where the ortholog is expected to be found in chimp and macaque harbor disabling mutations, which mean that the protein cannot be produced.…”
Section: Discussionmentioning
confidence: 99%
“…There are many examples in the literature of new genes with functionality in brain and testis (Burki and Kaessmann 2004;Emerson et al 2004;Begun et al 2007;Potrzebowski et al 2008;Rosso et al 2008;Zhou et al 2008). One of the novel genes is expressed in male reproductive tissue and one was identified in brain tissues, but they were also identified in many other tissues (Table 1) and there is no statistical trend.…”
Section: Sequence Characteristics and Expression Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…An important source of genetic variation for adapting to environmental stresses is that of gene duplication, a process by which most new genes are gained (Ohno 1970;Zhou et al 2008;Zhang et al 2009). Despite the fact that the rate of gene duplication is of the same order of magnitude as or higher than the rate of nucleotide mutation, duplicate genes are more likely to be lost than preserved (Li 1999;Sebat et al 2004;Lupski 2007;Emerson et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…One class of structural variant, termed copy number variation (CNV), includes deletions, duplications, insertions, and genomic rearrangements which affect the number of occurrences of a specific DNA sequence present in the genome . CNV is known to occur extensively in the Drosophila genome with functionally significant consequences (Bridges 1936;Dopman and Hartl 2007;Tibshirani and Wang 2008;Zhou et al 2008). In one study of 15 Drosophila strains, as many as 10% of genes were observed to harbor CNVs (Emerson et al 2008).…”
Section: Introductionmentioning
confidence: 99%